2017
DOI: 10.1186/s40176-017-0101-7
|View full text |Cite
|
Sign up to set email alerts
|

Can public works programs reduce youth crime? Evidence from Papua New Guinea’s Urban Youth Employment Project

Abstract: Crime rates in Papua

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The same study found no significant impact on adolescents involved in assaults and trespassing (Ivaschenko et al, 2017).…”
Section: Null Effectmentioning
confidence: 83%
See 1 more Smart Citation
“…The same study found no significant impact on adolescents involved in assaults and trespassing (Ivaschenko et al, 2017).…”
Section: Null Effectmentioning
confidence: 83%
“…In Papua New Guinea, the cash for work programme reduced participants' frequency of threatening to use force by 13 percentage points, and of fighting back in response to an attack by 11 percentage points, which correspond to 65 and 25% reductions, respectively, relative to the baseline (Ivaschenko et al, 2017).…”
Section: Youth Violence Reductionmentioning
confidence: 99%
“…Dasgupta, Gawande, and Kapur (2017) also show that the roll-out of India's National Rural Employment Guarantee Scheme can cause a large long-run reduction in Maoist conflict violence. And for programs with very similar features in Papua New Guinea (two months of public works employment for out-of-school youth, combined with six months of classroom and on-the-job training), Ivaschenko et al (2017) have found that project participants became less likely to hang out with friends at night, and less likely to have friends involved in crime, and involved in fights or robberies. However, it presents little robust evidence that the program reduces participants' engagement in or exposure to crime.…”
Section: Literature Reviewmentioning
confidence: 98%
“…As mentioned in the Introduction, very few specific studies focus on the crime effects of public works programs (Alzua, 2011; Dasgupta et al., 2017; Ivaschenko et al., 2017), finding mixed evidence, and of which only Dasgupta et al. (2017) undertake a similar methodological approach relying on panel data for program exposure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And for programs with very similar features in Papua New Guinea (2 months of public works employment for out‐of‐school youth combined with 6 months of classroom and on‐the‐job training), Ivaschenko et al. (2017) have found that project participants became less likely to hang out with friends at night and less likely to have friends involved in crime, fights, or robberies. However, it presents little robust evidence that the program reduces participants’ engagement in or exposure to crime.…”
Section: Introductionmentioning
confidence: 99%